Myocardial damage after continuous aerobic and anaerobic exercise in rats (Faculty of Medicine Universitas Indonesia, 2013)
Background: Regular physical activity is highly recommended in preventive, curative, and rehabilitative programs in order to promote health, especially cardiovascular health. However, physical activity can also cause sudden death. In athletes, sudden death may occur during sport competitions, with myocardial infarction as the most common etiology. It is suspected that continuous training without any rest-day play a role in cardiac muscle damage and sudden death during competition. Our study was aimed to learn about cardiac muscle adaptation on continuous aerobic and anaerobic physical activity without any rest-day. Methods: The specimens in our study were cardiac muscle tissue obtained from rats that had performed aerobic and anaerobic physical activity on treadmill for 1, 3, 7, and 10 days without any rest-day. Blood gas analysis and hematological assessment were used as parameters of systemic adaptation to hypoxia during physical activity. Moreover, histopathology of cardiac muscle tissue was performed as parameter for cardiac muscle damage. Results: The results showed that aerobic and anaerobic physical activity caused a systemic hypoxic condition and triggered adaptation responses. Cardiac muscle damage occurred on the 10th day in both treatment groups, with more severe damage observed in the group with anaerobic physical activity. The tissue protein level in the anaerobic group increased progressively on the 10th day. Conclusion: Physical activity may result in hypoxia and systemic adaptation. Aerobic and anaerobic physical activities performed for 10 days without any rest-day may cause cardiac muscle damage. (Med J Indones. 2013;22:209-14. doi: 10.13181/mji.v22i4.601)